Удосконалення технології окислювального хлорування етилену на каталізаторах Cu(І)(ІІ)/γ-Аl2О3 - Микитин, Ігор Михайлович (Національний університет "Львівська політехніка", 2009)
Дисертацію присвячено удосконаленню промислової технології одержання 1,2-дихлоретану окислювальним хлоруванням етилену на каталізаторах Cu(І)(ІІ)/γ-Аl2О3. Виявлено шляхи забруднення каталізатора окислювального хлорування етилену сполуками заліза. Вивчено умови дезактивації та регенерації частково дезактивованого каталізатора окислювального хлорування етилену. Встановлено будову активних центрів каталізаторів окислювального хлорування етилену ([СuСl4]-2, [СuСl2]-1) на поверхні γ-Аl2О3 нанесеного і просякнутого типів відповідних промислових марок “Харшоу” (Х1) і “Монтекатіні” MEDC-B. Запропоновано новий механізм металокомплексного каталізу реакції окислювального хлорування етилену з участю поверхневих металокомплексів Al2O3[СuСl4]-2, Al2O3[СuСl2]-1 в реакції з етиленом, хлористим воднем і киснем. Запропоновано удосконалення технології окислювального хлорування етилену в 1,2-дихлоретан шляхом додаткового охолодження циркуляційного газу до температури +2 –  +5 °С з відділенням залишків 1–4 % 1,2-дихлоретану із циркуляційного газу та новий спосіб приготування каталізатора окислювального хлорування етилену в 1,2-дихлоретан із вмістом активних компонентів – СuСl2·К+, Мg+2 – 4–8 % на поверхні Аl2О3/SіО2 (20–40 % Аl2О3). Диссертация посвящена усовершенствованию промышленной технологии получения 1,2-дихлорэтана окислительным хлорированием этилена на катализаторах Cu(І)(ІІ)/γ-Аl2О3. Выявлены пути загрязнения катализатора окислительного хлорирования этилена соединениями железа. Исследованы условия дезактивации и регенерации частично дезактивированного катализатора окислительного хлорирования этилена. Предложено строение активных центров катализаторов окислительного хлорирования этилена ([СuСl4]-2, [СuСl2]-1) на поверхности γ-Аl2О3 нанесенного и пропитанного типов соответствующих промышленных катализаторов марок “Харшоу” (Х1) и MEDC-B. Разработан новый механизм металокомплексного катализа реакции окислительного хлорирования этилена с участием поверхностных металокомплексов Al2O3[СuСl4]-2, Al2O3[СuСl2]-1 в реакции с этиленом, хлористым водородом и кислородом. Предложено усовершенствование технологии окислительного хлорирования этилена в 1,2-дихлорэтан путем дополнительного охлаждения циркуляционного газа к температуре +2 – +5 °С с отделением остатков 1–4 % 1,2-дихлорэтана из циркуляционного газа. Предложен новый способ получения катализатора окислительного хлорирования этилена в 1,2-дихлорэтан с содержанием активных компонентов – СuСl2·К+, Мg+2 – 4–8 % на поверхности Аl2О3/SіО2 (20–40 % Аl2О3).The thesis is devoted to the improvement of the industrial technology of obtaining 1.2-dichlorethane by means of ethylene oxidizing chlorination on catalysts Cu(І)(ІІ)/γ-Аl2О3. The activity of catalysts of different firms (Engelhard, BASF, Rhône-Poulenc, COHDEA, Montecatini, Harshow, Montedison) is studied, and the most effective catalyst of MEDC-B grade is selected. 2 year’s inspection of ethylene oxidizing chlorination reactors has shown that the industrial catalyst gets ground in the ethylene oxidizing chlorination reactor after its working for 60 through 100 days, and its characteristics change. Stable work is observed during 60 through 270 days, upon which the characteristics of the catalyst are considerably changed, i.e. the activity and selectivity decrease, and the granulometric composition changes, and then the regeneration becomes necessary. The ways of contamination of the ethylene oxidizing chlorination catalyst by iron compounds are discovered. The optimum correlation of НСl:С2Н4 within the range of (2–2,1):1 is also proposed, which makes it possible to achieve optimum efficiency concerning НСl and С2Н4 (96,0–99,0 % and 95,3–95,5 %, respectively). The possibility of the regeneration of the partly deactivated ethylene oxidizing chlorination catalyst is studied. The regeneration in an oxygen mode (30–40 % О2) is more effective than in an air mode (20 % О2). The formation of active centers of ethylene oxidizing chlorination catalysts ([СuСl4]-2, [СuСl2]-1) on the surface γ-Аl2О3 of applied and impregnated types, Harshow X1 and MEDC-B industrial marks, respectively, is proposed. The new mechanism of the metal complex catalysis of ethylene oxidizing chlorination reaction with the help of surface metal complex Al2O3[СuСl4]-2, Al2O3[СuСl2]-1 reacting with ethylene, hydrogen chloride, and oxygen, is developed. The improvement of the technology of ethylene oxidizing chlorination in 1.2-dichlorethane by means of additionally cooling circulation gas to the temperature of +2 through +5 °C with the help of circulatory cooling agent (NaCl solution) with the temperature of -15 through -20 °C, the remains of 1–4 % 1.2-dichlorethane being scrubbed from circulation gas, is proposed. The new simplified method of preparing the ethylene oxidizing chlorination catalyst in 1.2-dichlorethane with the content of СuСl2·К+, Мg+2 – 4–8 % on the surface of Аl2О3/SіО2 (20–40 % Аl2О3), with S=100–150 m2/g, d = 30–110 mkm is proposed, which is the most optimum properties of the ethylene oxidizing chlorination catalyst.
Усовершенствование технологии окислительного хлорирования этилена на катализаторах Cu(І)(ІІ)/γ-Аl2О3
Improvement of the technologies of ethylene oxidizing chlorination on Cu(І)(ІІ)/γ-Аl2О3 catalysts
Keywords: 1.2-dichlorethane; oxidation; chlorination; chlorination; selectivity; reactor; components; structure; СuСl4]-2; СuСl2]-1; molar correlation; efficiency; concerning; ethylene; conversion; ethylene; chlorine hydride; oxygen; 1,2-дихлорэтан; окисление; хлорирование; активность; селективность; катализатор; этилен; хлористый водород; кислород; конверсия; 1,2-дихлоретан; окислення; хлорування; активність; селективність; каталізатор; етилен; хлороводень; кисень; конверсія